Scrappy memoir of a U.S. fighter pilot in Korea and Vietnam - Johnson, Howard C.; O'Connor, Ian A. (McFarland, 2008)
"From World War II to Vietnam, this memoir tells the story of fighter pilot, Howard C. "Scrappy" Johnson. Beginning in Knoxville, Tennessee, it follows Johnson through his student career at the University of Louisville and his enlistment as an Air Force cadet. Johnson served a tour of duty in Korea and ended up as director of operations in Vietnam"--Provided by publisher
River rats -- Growing up -- "Louavall" -- The Army Air Corps -- Laredo -- The big bang -- The Philippines -- The police action -- Back to the Philippines -- Cape Cod -- Way up North -- California -- Starfighter -- The Collier trophy -- The Luftwaffe -- The Tactical Air Command -- Hell -- Thailand -- In the beginning -- Korat confidential -- Stateside again -- Punchin' cattle -- Scalawag -- Finis
Keywords: Johnson, Howard C. / 1920-; Johnson, Howard C. <1920->; United States / Air Force / Officers / Biography; United States. -- Air Force -- Officers -- Biography; Fighter pilots / United States / Biography; Vietnam War, 1961-1975 / Personal narratives, American; Korean War, 1950-1953 / Personal narratives, American; World War, 1939-1945 / Personal narratives, American; Vietnamkrieg; Weltkrieg (1939-1945); Fighter pilots -- United States -- Biography; Korean War, 1950-1953 -- Personal narratives, American; Vietnam War, 1961-1975 -- Personal narratives, American; World War, 1939-1945 -- Personal narratives, American; Flugzeugführer; Luftwaffe; USA; Biografie; Erlebnisbericht